KAJIAN DAN PENGARUH POSITIF NEGATIF PENJAJAHAN KOLONIAL BELANDA TERHADAP PEMBENTUKAN NEGARA INDONESIA - Leonard Tasuno Laiya; Rasji Rasji (Jurnal Hukum Adigama, 2022)
The colonial period in Indonesia did not begin immediately when the Dutch arrived in the archipelago at the end ofthe 16th century. On the other hand, the Dutch colonization process was a protracted process of political expansionthat spanned many centuries before reaching the present-day limits of Indonesia. Following the demise of theMataram Sultanate in the 18th century, the Vereenigde Oost-Indische Compagnie (VOC) established itself as aneconomic and political force on the island of Java. Since the early 1600s, this Dutch trading corporation had been adominant power in Asian commerce, but in the 18th century, it developed an interest in interfering in indigenouspolitics on the Indonesian island of Java in order to extend its grip over the local economy. However, corruption,inept administration, and severe rivalry from the British (East India Company) contributed to the VOC's demisetowards the end of the 18th century. Finally bankrupt in 1796, the VOC was seized by the Dutch government. As aresult, the Dutch crown acquired the VOC's property (assets) in the archipelago in 1800. Between 1806 and 1815,when the French conquered the Netherlands, these assets were given to the British. Following Napoleon's defeat atWaterloo, it was determined that the Dutch would reclaim the majority of the archipelago.